The impact of self-evaluation of public school principals in Jordan on leadership practices and the quality of education from the point of view of school principals themselves – A field study on secondary school principals – Amman – - Alsoud, Khitam Abdalhameed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the impact of self-evaluation of secondary school principals in the Kasbah of Oman on leadership practices and the quality of education from the point of view of the principals themselves. The sample of the study consisted of all (39) secondary school principals of the Directorate of Education of the Kasbah of Amman. The results of the study showed that the overall arithmetic average of the study sample estimates for the effect of self-evaluation of school principals was (4.14) with a high evaluation score. The mean dimensions of the self-evaluation ranged between (3.82 - 4.14), where it came after the quality of leadership practices ranked first with an average of (4.14). With a high evaluation score, followed by second place after the quality of the learning process with an arithmetic average (4.00) and a high evaluation score, and in third place the quality of teaching with an arithmetic average (3.94) and a high evaluation score, and in the fourth place the quality of students’ performance with an arithmetic average (3.84) and a high assessment score. , And last ranked c Dah school environment, an arithmetic mean (3.82) and highly evaluated high, These results indicate that there is a high impact of self-evaluation among secondary school principals in the Kasbah of Oman and education on leadership practices and quality of education. In light of these results, the study recommended the importance of self-evaluation of administrative and educational leadership practices and the quality of education.